2018
DOI: 10.1111/eci.12998
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids supplementation impairs anti‐oxidant high‐density lipoprotein function in heart failure

Abstract: BackgroundThe underlying reasons for the highly inconsistent clinical outcome data for omega‐3‐polyunsaturated fatty acids (n3‐PUFAs) supplementation in patients with cardiac disease have not been understood yet. The aim of this prospective, randomized, double‐blind, placebo controlled study was to determine the effects of oral treatment with n3‐PUFAs on the anti‐oxidant capacity of HDL in heart failure (HF) patients.MethodsA total of 40 patients with advanced HF of nonischaemic origin, defined by NT‐proBNP le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Recently, Sherrat et al ( 59 ), when assessing HDL particle oxidation upon induction by copper and in the absence of LDL, observed greater power of EPA, relative to DHA, in delaying the onset of oxidation ( 59 ). In humans, Wurm et al ( 60 ) showed that after 12 weeks, the antioxidant function of HDL, as measured by the HDL inflammatory index, was significantly impaired in the group supplemented with ω-3 in a dose-dependent manner ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sherrat et al ( 59 ), when assessing HDL particle oxidation upon induction by copper and in the absence of LDL, observed greater power of EPA, relative to DHA, in delaying the onset of oxidation ( 59 ). In humans, Wurm et al ( 60 ) showed that after 12 weeks, the antioxidant function of HDL, as measured by the HDL inflammatory index, was significantly impaired in the group supplemented with ω-3 in a dose-dependent manner ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a small, double-blind, placebo-controlled, randomized study, the effect of n-3 PUFA supplementation on the high-density lipoprotein (HDL) antioxidant capacity was investigated. This study arose from the knowledge of the oxidative stress involvement in HF pathogenesis [ 77 ]. In fact, the association between the HDL antioxidant properties, HF, and clinical outcome was demonstrated.…”
Section: Heart Failure and Pufasmentioning
confidence: 99%
“…In fact, the association between the HDL antioxidant properties, HF, and clinical outcome was demonstrated. In addition, in some studies, an increase in HDL levels has been reported in HF patients following integration with n-3 PUFAs, with a consequent reduction in the risk of cardiovascular events (CVD) [ 77 ]. In this study, 40 subjects with advanced HF of non-ischemic origin, New York Heart Association (NYHA) class III or IV, who had been on therapy for three months or more were treated with 1 or 4 g of n-3 PUFAs per day for 12 weeks.…”
Section: Heart Failure and Pufasmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] A study by Wurm et al reported controversial results by showing that n3-PUFA supplementation diminishes the anti-oxidant function of HDL in nonischemic HF patients. [44] These divisive results demand further extensive studies and information in this regard.…”
Section: Inflammatory Factors and Plasma Lipidsmentioning
confidence: 99%